(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2016)
The world tendencies of energy efficient policy are considered in the article, the features of functioning of the regional energy systems are outlined, defined the role of energy exchanges in the unique European energy market development, summarizing conclusions are done in relation to implementation of the world experience of energy efficiency during transformation processes in Ukraine.